Efektifitas Respon Sensor Proximity Induktif dalam Menyortir Pecahan Logam pada Model Conveyor - Alfian Djafar; Rizaldy Gunawan; Hadhimas Dwi Haryono; Doddy Suanggana (Fakultas Teknik, 2023)
Mining commodities such as coal, gold, copper, and other mining products are closely related to the use of conveyors. In the material handling process, metal shards follow into the bulk material. This incident can cause damage to the crusher teeth. Therefore, this study developed a conveyor with a metal impurity sorting system. To detect, the sensor used is an inductive proximity sensor. When Mining material moves from the head pulley to the tail pulley, the inductive proximity sensor detects metal shards. The proximity sensor detects metal shards to be input, and then the Arduino Uno orders the servo motor to move the sorting lever. The independent variables used are mining materials and metal shards. The mining materials are used in the form of coal, sand, and rock. At the same time, the metal shards are iron (Fe), Copper (Cu), and Aluminum (Al). The dependent variable used is the response effectiveness of the metal sorter. Based on the study's results, the conclusion is that the proximity sensor can work well. The inductive proximity sensor can detect metal shards with a success rate of 92.59%. When the sensor detects metal impurities, instructions will be given to the servo motor and actuate the sorting lever. The success rate of the sorting lever that pushes and separates metal impurities from the mining material is 88.89%.